2014
DOI: 10.4028/www.scientific.net/amr.931-932.588
|View full text |Cite
|
Sign up to set email alerts
|

Motorcyclist's Helmet Wearing Detection Using Image Processing

Abstract: Motorcycle accidents have been rapidly growing throughout the years in many countries. Due to various social and economic factors, this type of vehicle is becoming increasingly popular. The helmet is the main safety equipment of motorcyclists but many drivers do not use it. If a motorcyclist is without helmet an accident can be fatal. This paper presented an automatic method for vehicle detection, motorcycles classification on public roads and a system for automatic detection of motorcyclists without helmet. F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 11 publications
0
12
0
Order By: Relevance
“…Marayatr et al used the area feature to classify motorcycles and other vehicles [10]. This feature was classified using MLP.…”
Section: Motorcycle Detectionmentioning
confidence: 99%
See 1 more Smart Citation
“…Marayatr et al used the area feature to classify motorcycles and other vehicles [10]. This feature was classified using MLP.…”
Section: Motorcycle Detectionmentioning
confidence: 99%
“…Marayatr and Kumhon used the circular hough transform (CHT) descriptor for helmetless head detection. The result showed that it was found erroneous for the detection of 2 or more passengers [10]. Silva et al proposed the HOG descriptor, and the dataset for the study was taken in a static environment [4].…”
Section: Helmetless Head Detectionmentioning
confidence: 99%
“…The last step involves helmet detection. Colour based and circle Hough transform is used to detect helmet [7], [5], [10] and HOG descriptors can also be used for helmet detection [22]. Colour feature recognition is another option [15].…”
Section: Detection Of Non-helmet Riders and Extraction Of License Plamentioning
confidence: 99%
“…From these recordings, ships detection is performed, notably those exercising illegal fishing. As technologies develop nowadays, digital image processing techniques and artificial intelligence can be used for analysis of the object on digital image such as for motorcycle detection [2][3][4], renal tumor detection [5], traffic monitoring [6], virtual reality robot [7], motorcyclist's helmet wearing detection [8], blood typing [9], cotton pests detection [10], rice variety identification [11] and analysis of road damage [12]. Meanwhile, the studies on ship detection have been complied by percolating several methods, such as Support Vector Machine (SVM) [13][14], visual saliency and histogram [15], Discrete Wavelet Transform (DWT) [16], combination statistical methods, mathematical morphology and other signalprocessing techniques [17], and sea surface analysis [18].…”
Section: Introductionmentioning
confidence: 99%